Performance of Small and Medium-sized Enterprises in Uganda: the Role of Innovation - Okumu, Ibrahim Mike; Buyinza, Faisal (AERC., 2020)
Using the 2013 World Bank Enterprise Survey data for Uganda, this paper employs the quintile estimation technique to explain the relationship between innovation and firm performance in small and medium-sized enterprises (SMEs). Innovation involves the introduction of a new or significantly improved production process, product, marketing technique or organizational structure. Our results indicate that individual processing, product, marketing and organizational innovations have no impact on labour productivity as proxied by sales per worker. However, the results indicate the presence of complementarity between the four types of innovation. Specifically, the effect of innovation on sales per worker is positive when an SME engages in all four types of innovation. Even then the complementarity is weakly positive with incidences of a negative relationship when using any combination of innovations that are less than the four types of innovation. Policy-wise the results suggest that efforts to incentivize innovation should be inclusive enough to encourage all four forms of innovation.
Keywords: Innovation; firm performance; business environment; Uganda